Answer:
length= 3.7 ft.
Explanation:
T= (square root of length) * k
1.8 seconds = (square root of 3) * k
k= 1.8 seconds / (square root of 3)
a.) T= (square root of 11) k
substituting k:
T=(square root of 11) * 1.8 seconds / (square of 3)
T= 3.4 seconds
b.) 2 seconds = (square root of length) k
substituting k:
2 seconds =(square root of length) 1.8 seconds / (square root of 3)
Divide the equation by 1.8 seconds / (square root of 3):
2 seconds / [1.8 seconds / (square root of 3)] = (square root of length)
10(square root of 3) / 9 = (square root of length)
square both sides:
100/7 ft= length
length= 3.7 ft.
Hope this helps.